KEPUTUSAN PEMBELIAN BERDASARKAN KUALITAS PELAYANAN, HARGA DAN ATMOSFER CAFE: PENGUJIAN EMPIRIS PADA MAKTUN KOPI LAMONGAN - Rizky Wahyudha Rosiawan; Adi Lukman Hakim; Rifqi Kharisma Ramadhan (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the effect of service quality, price and cafe atmosphere on purchasing decisions (case study on Maktun Kopi in Lamongan city). This study uses a quantitative method with a sample of 100 respondents with the help of IBM SPSS 26 data processing. The results of this study indicate that partially the service quality variable has a positive and significant effect on purchasing decisions with a t-value of 2.952 which is greater than the t table of 1.660, partially the price variable has a positive and significant effect on purchasing decisions with a t-value of 3.942 which is greater than the t table of 1.660, partially the Cafe atmosphere variable has a positive and significant effect on purchasing decisions with a t-value of 4.606 which is greater than the t table of 1.660, simultaneously the influence of service quality, price and Cafe Atmosphere have a positive and significant effect on purchasing decisions (case study on Maktun Kopi in Lamongan city) with an F count of 34.955 more than F table 2.699